2016
DOI: 10.1097/bsd.0000000000000112
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Sealer Device Reduces Blood Loss and Transfusion Requirements in Posterior Spinal Fusion for Degenerative Lumbar Scoliosis

Abstract: Utilization of a bipolar sealer during correction of lumbar degenerative scoliosis may offer comparable hemostatic effects, without prohibitive cost or adverse drug-related risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…In another study by Wang and colleagues, they showed that using bipolar electrocautery or bipolar sealer for lumbar degenerative scoliosis surgeries leads to significantly reduced bleeding compared to using standard or monopolar electrocautery (26). These results differ from our study results, which may be due to the difference in the age of the patients and the type of the surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…In another study by Wang and colleagues, they showed that using bipolar electrocautery or bipolar sealer for lumbar degenerative scoliosis surgeries leads to significantly reduced bleeding compared to using standard or monopolar electrocautery (26). These results differ from our study results, which may be due to the difference in the age of the patients and the type of the surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, we identified 12 RCTs with 1130 patients (bipolar sealer = 555, standard electrocautery = 575) that were associated with orthopedic surgery [11,12,23,32] (Figure 1). A total of 6 studies involved THA [11,28,32], 3 studies involved TKA [12,23,24], and 3 studies involved spinal surgery [25,27]. The number of patients included in the studies ranged from 25 to 100.…”
Section: Search Resultsmentioning
confidence: 99%
“…Because it was impossible to blind the participants and surgeons who performed the surgery, all outcomes had an unclear risk of bias for this domain [11,12,23,32]. The detection bias was low in 6 studies [11,23,25,28,30], and the rest had unclear risk bias [12,24,26,27,31,32]. Attrition bias, reporting bias and other biases were low in 9 studies [11,12,23,25,28,32] and the remaining 3 studies all had unclear bias [24,26,27].…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The impetus on spine surgeons to transition to the outpatient setting has been spurred by minimally invasive and less exposure surgery techniques (4, 9,11,14). Several studies have demonstrated the use of transexemic acid, bipolar sealer devices in reducing blood loss and transfusion requirement in surgery for scoliosis (15,16). Other outpatient studies are available demonstrating surgical techniques with excellent or equivocal outcomes to inpatient surgery, with comparison of blood loss (3-5).…”
Section: Discussionmentioning
confidence: 99%